Islamic Philanthrophy And Economic Development Of The Umum - Jamal, Ahmad Jamali; Ana, Indah Yuliana (Jurnal Ilmiah Ekonomi Islam, 2024)
Islamic philanthropy has meaning and has a very significant role in the economic development and development of the people both in the form of empowerment and utilization. The aim of preparing this paper is to see to what extent the concept of philanthropy can improve the people's economy. And the results of this research show that the presence of philanthropy can be an instrument for alleviating poverty which is increasing in today's society. Management of philanthropic funds by social institutions can reduce poverty and social inequality and can pump up people's enthusiasm to improve prosperity. Keywords: Philanthropy, Poverty, Community Economy and Empowerment.